2013
DOI: 10.1086/668686
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Plant Concept and Environment Reconstruction of aTelemachusConifer (Voltziales) from the Triassic of Antarctica

Abstract: We present a whole-plant concept for a genus of voltzialean conifers on the basis of compression/impression and permineralized material from the Triassic of Antarctica. The reconstruction of the individual organs is based on a combination of organic connections, structural correspondences, similarities in cuticles and epidermal morphologies, co-occurrence data, and ex situ palynology. The affiliated genera of organs include trunks, branches, and roots (Notophytum); strap-shaped leaves with parallel venation (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 65 publications
1
54
1
2
Order By: Relevance
“…Recientemente, se ha publicado una reconstrucción de la planta completa de una Voltziaceae del Triásico de Antártida, que vincula órganos con diferentes modos de preservación y que a su vez previamente habían sido relacionados a diversas familias (Escapa et al, 2010;Bomfl eur et al, 2013) Jersey, 1962). Sin embargo, la vinculación de estos órganos presenta algunas difi cultades, en particular porque no todos provienen de la misma unidad estratigráfi ca, y entre ellos existen diferencias signifi cativas a nivel anatómico, como es el caso de N. kraeuselii y P. aequata.…”
Section: Heidiphyllum Minutifoliumunclassified
See 1 more Smart Citation
“…Recientemente, se ha publicado una reconstrucción de la planta completa de una Voltziaceae del Triásico de Antártida, que vincula órganos con diferentes modos de preservación y que a su vez previamente habían sido relacionados a diversas familias (Escapa et al, 2010;Bomfl eur et al, 2013) Jersey, 1962). Sin embargo, la vinculación de estos órganos presenta algunas difi cultades, en particular porque no todos provienen de la misma unidad estratigráfi ca, y entre ellos existen diferencias signifi cativas a nivel anatómico, como es el caso de N. kraeuselii y P. aequata.…”
Section: Heidiphyllum Minutifoliumunclassified
“…Anatómicamente, el xilema secundario de las Voltziales triásicas y de las Pinales podría presentar similitudes. De hecho, en otras regiones del Gondwana, se ha sugerido una reconstrucción en la que se vincula a Heidiphyllum/ Telemachus con troncos permineralizados, de características semejantes a los leños de las podocarpáceas (Axsmith et al, 1998;Escapa et al, 2010;Bomfl eur et al, 2013).…”
Section: Introductionunclassified
“…This kind of preservation is exceedingly rare or unknown in all of the co-occurring gymnosperm foliage types (table 1). In addition, we found that detached petriellalean foliage in the Antarctic collections is always strongly fragmented and have never observed complete and isolated leaves, which, by contrast, is the common mode of leaf preservation of the co-occurring gymnosperms (Bomfleur , 2013aEscapa et al 2011). Furthermore, petriellalean compression fossils are overall notably rare, occurring in only 2 of 49 or more plant-fossil assemblages surveyed.…”
Section: Habit Reconstructionmentioning
confidence: 84%
“…Furthermore, petriellalean compression fossils are overall notably rare, occurring in only 2 of 49 or more plant-fossil assemblages surveyed. They are absent in the typical "leaf-litter assemblages"-which accumulated during quiescent conditions through the physiological loss of leaves and reproductive organs of seasonally deciduous gymnosperm trees (table 1; Bomfleur et al 2011Bomfleur et al , 2013a)-and are preserved only in rather unusual plant-fossil assemblages; plant level 2 from the Allan Hills, for example, contains redeposited, complete fern rhizomes with attached fronds and croziers (T. N. Phipps et al 1998), subterranean organs of sphenophytes (Bomfleur et al 2013b), and abundant debris of leafy and thallose bryophytes (Bomfleur et al 2014a). At the Alfie's Elbow site, petriellalean remains occur only in the level 2 bed, which also yielded (1) the only known occurrence of corystosperm reproductive organs attached to short shoots Axsmith et al 2000Axsmith et al , 2007, (2) one of only three known occurrences worldwide of attached Dicroidium leaves (Axsmith et al 2000), and (3) the only known record of dipterid ferns in the Antarctic Triassic (Escapa et al 2011).…”
Section: Habit Reconstructionmentioning
confidence: 99%
“…Pteruchus-like pollen is known from the Upper Permian through Lower Jurassic (Balme 1995) and the fructification had wide geographic extent in the Gondwanan Triassic (chiefly, Anisian-Norian: Anderson & Anderson 2003). Alisporites pollen has been affiliated with conifers and possibly ginkgophytes (Balme 1995, Bomfleur et al 2013 and has been identified from the Permian through Upper Cretaceous (Mohr & Gee 1992, Balme 1995.…”
Section: Triassic Pteridospermsmentioning
confidence: 99%